Frequency of Perineal Trauma in Women Undergoing Spontaneous vs Directed Valsalva Type Pushing in Labour - Fatima Ayub, Nilofar Mustafa, Pakeeza Aslam, Rehana Kanwal, Qurutulain Mushtaq, Shazia Tufail, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the frequency of perineal trauma in women undergoing the spontaneous vs the Valsalva-type pushing in the second stage of labour. Study Design: Randomized controlled trial Duration of Study with Dates: The study was carried out from 15-12-2020 to 19-03-2021. Setting: Department of Obstetrics and Gynaecology, Combined Military Hospital, Lahore.National University of Medical Sciences NUMS. Material and Methods: A total of 154 labouring females were enrolled in the study. These females were randomly assigned to one of two groups, A (the Valsava-type pushing method group) and B (the spontaneous pushing group). After the delivery of the placenta, the patients were all examined for any perineal trauma as per the operational definition. Results: Patients ranged between 18-40 years of age with a mean age of 26.3±4.0 years in Group A and 27.0±3.3 years in Group B. All the patients were between 38-40 weeks of gestation at the time of enrollment with mean gestational age being 39±0.7 weeks for group A and 38.9±0.7 for group B. There were 61 primigravida (39.6%, 34 in Group A and 27 in Group B) and 93 multigravida (60.4%, 43 in Group A and 50 in Group B). All women delivered vaginally in the cephalic presentation. The mean length of the second stage of labor was 25.7±29.0 min for the Valsalva pushing group and 31.6±37.5 min for the spontaneous pushing group. The mean fetal weight was 3.1±0.3 kg for both groups. 43 (55.8%) patients in the Valsalva pushing group and 46 (59.7%) in the spontaneous pushing group underwent an episiotomy during delivery. 9 (11.7%) patients in each group sustained perineal trauma (x2 = 0.0, p = 1.0). No one in the sample suffered greater than a second degree laceration. Out of the nine patients that did incur perineal trauma in the Valsalva type pushing group, 4 (44.4%) were first degree perineal tears and 5 (55.6%) were second degree perineal tears while among those in the spontaneous pushing group, 2 (22.3%) fell in the first degree tear category and 7 (77.7%) in the second degree tear category (x2 = 1.0, p = 0.317). Conclusion: Our findings suggest that there is no association between the rate of perineal trauma among patients who underwent the directed Valsalva- type method of pushing and those that employed the spontaneous pushing method during the second stage of labour. Keywords: Perineal trauma, Perineal tears, Second stage of labour, Pushing methods in labour, Valsalva- type pushing, Directed pushing, Spontaneous pushing